Pengaruh Kinerja Keuangan, Ukuran Perusahaan, dan Leverage terhadap Perencanaan Pajak - Austin, Irene; Kezia Josephine (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effect of financial performance, firm size, and leverage on tax planning proxied by the Effective Tax Rate (ETR) in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research is motivated by the importance of tax planning strategies in improving company efficiency without violating applicable tax regulations. The independent variables used in this study are financial performance proxied by ROA, firm size measured using Ln Total Assets, and leverage measured using the DER. Meanwhile, the dependent variable is tax planning proxied by the ETR. This study uses a quantitative method with secondary data obtained from annual reports and financial statements of mining sector companies listed on the IDX. The sampling technique used purposive sampling, resulting in 120 final observation data. Data analysis was conducted using SPSS 27 through descriptive statistical tests, classical assumption tests, multiple linear regression analysis, coefficient of determination tests, simultaneous tests (F-test), and partial tests (t-test). This study concludes that leverage is the most influential factor affecting tax planning in mining sector companies, while financial performance and firm size are not able to significantly influence corporate tax planning policies.